Drug Resistant Profile among the Pulmonary Tuberculosis Patients at Waled General Hospital, Cirebon Regency, Indonesia - Desy Syafira Santoso; Dwi Rosa Eka Agustina; Nihayahatul Amaliyah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Tuberculosis (TB) is an infectious bacterial disease caused by Mycobacterium tuberculosis, most commonly affecting the lungs. Drug Resistance Tuberculosis (DR-TB) is a TB disease resistant to one or more anti-tuberculosis drugs. In a global report in 2022, Indonesia ranked 5th for the burden of drug-resistant tuberculosis (DR-TB), and in the tuberculosis information system (SITB) data in West Java is one of the provinces with TB-RO case finding coverage that exceeds the national target with a percentage of 78%. Aim: To determine the profile of drug-resistant pulmonary tuberculosis patients at Waled General Hospital, Cirebon Regency between 2022 and 2023. Methods: This study used a retrospective descriptive method. Sampling was done using a total sampling technique, and a sample of 43 respondents was obtained. Data were collected through medical records and tuberculosis information system (SITB) and then analyzed by univariate statistics without comparisons or association tests. Results: Based on socio-demographic characteristics, the majority of patients aged 46-55 years were 12(27.9%), patients with the most gender were male totaling 29(67.4%), patients with the most recent education were elementary school and high school had the same number of 15(34.9%), most patients' occupations were working at 32(74.4%). The most common classification of DR-TB is MDR-TB, totaling 35(81.4%), the history of previous tuberculosis treatment is mostly new patients at 18(41.3%), and most patients do not have comorbidities totaling 19(44.2%). Conclusion: The profile of patients with DR-TB based on socio-demographics at Waled General Hospital, Cirebon between 2022 and 2023 is mainly aged 19-59 years with the most gender is male, the last education of elementary and high school has the same number, most patients work. Most patients with previous TB treatment histories were new, and most did not have comorbidities. A comprehensive approach to DR-TB control should incorporate; public education on treatment adherence, enhanced case management and surveillance, and consistent application of molecular diagnostics. Such measures may effectively decrease DR-TB prevalence and associated mortality. This study further highlights the importance of TB awareness and environmental hygiene in Indonesia's ongoing TB elimination efforts.